Distance learning in cardiology: the use of multimedia clinical diagnostic tasks - S. I. Karas; E. V. Grakova; M. V. Balakhonova; M. B. Arzhanik; E. E. Kara-Sal (Российский кардиологический журнал)
Aim. To create a methodological base for distance learning of cardiology healthcare professionals — multimedia clinical diagnostic tasks.Material and methods. The interdisciplinary team used text and multimedia formats for clinical diagnostic data. Web technologies provided remote access to information located on the server.Results. The report presents the experience of the practical implementation of multimedia clinical diagnostic tasks in cardiology, including the augmented reality. The variability of presenting information to students is implemented in the multimedia clinical diagnostic tasks, which is integrated with the rating system for evaluating decisions. The solution paths are determined by the actions of the students in the trigger interactive blocks and is evaluated by the rating system. Personal rating is a numerical value that integrally characterizes the decisionmaking competence of students. The conversion of the quantitative rating into the conventional form (‘pass/fail’, ‘excellent’, ‘good’, ‘passing grade’) will be provided after the trial period of the software.Conclusion. The created Web service and computer simulations can become a methodological basis for the distance learning in cardiology. This technology can be in demand in the continuing medical education.